Pengaruh Pergantian Manajemen, Opini Audit, Ukuran KAP dan Auditfee Terhadap Auditor switching (Studi Kasus pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Kinanti Septina dewi; Djoko Kristianto (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Auditor switching is an action of the company in changing auditors or Public Accounting Firms that aims to maintain auditors' independence so that they remain objective in auditing clients' financial statements. The purpose of this study is to find out the significance of Management Change, Audit Opinion, Size of Public Accounting Firms, and Audit fees for Auditor switching. This study uses a type of quantitative data with the data source used is secondary data, namely annual financial statements accessed through the official website of the Indonesia Stock Exchange for the 2019-2023 period. The total population of this study is 70 companies and the sampling method uses the purposive sampling technique so that the number of samples that meet the criteria is 26 companies. The data collection method used is a documentation technique. The analysis techniques used are descriptive statistical tests, logistic regression analysis, and hypothesis tests. The results of the study found that management change had a significant positive effect on switching auditors, audit opinions did not have a significant effect on switching auditors, the size of public accounting firms had a significant negative effect on switching auditors and audit fees had no effect on switching auditors in infrastructure companies listed on the Indonesia Stock Exchange for the 2019-2023 period.